EXPERIMENTAL MEASURES OF THE EFFECTIVE HEAT TRANSFER COEFFICIENTS IN AIR BLAST FREEZERS FOR THE PROCESSING OF FRUIT PULPS - Resende, J. V.; Silveira Junior, V.; Neves Filho, L. (Revista de Engenharia Térmica, 2003)
The effective surface heat transfer coefficients during air blast freezing of plastic polyethylene packages containing fruit pulp models conditioned inside multi layer boxes were evaluated under conditions encountered in commercial practice. The results were presented as dimensionless correlations based on hydraulic diameter of the rectangular ducts. The effects on the surface heat transfer coefficient of the air temperature, air velocity, transducer position inside the boxes and box position in the pillage on the surface were analyzed. The results show: the effect of air-cooling temperature on the surface heat transfer is negligible in the range encountered in blast freezing practice. The effective surface heat transfer coefficients predicted by the non-dimensional correlations based on hydraulic diameter was successfully used to represent the bed irregularities, mainly in arrays of 5 and 3 layers. The effective surface heat transfer coefficients varied according to the position between the top and the bottom of the boxes and was influenced by the number of layers in the arrays.